It is the duty of every teacher to improve the speaking and listening processes of primary school children - Esparza, Gladys; Solano, Carolina (Rastros Rostros, 2023)
The school and the classroom are permanently linguistic environments par excellence; whether in the aesthetic education class, mathematics class or, even more so, in the mother tongue, students are confronted, almost all day long, with the language of the teacher and classmates and with the written texts. In a certain sense, in our context, teaching and learning in general is inconceivable without language. It is conversation and listening to explanations, expositions and debates, answers to questions, repetitions, paraphrases, summaries. Practically every teacher, in any area, is a teacher of spoken and written language.
Keywords: speaking; listening; primary school